DEVELOPING PRE-SERVICE MATHEMATICS TEACHERS’ UNDERSTANDING OF METRIC AND TOPOLOGICAL SPACES USING REFLECTIVE QUESTIONS - Deogratias, Emmanuel (International Online Journal of Education and Teaching, 2022)
This paper presents the ways that reflective questions were used to develop pre-service mathematics teachers’ understanding of metric and topological spaces. In particular, the purpose of developing PSTs’ understanding of metric and topological spaces is that understanding these mathematical concepts leads to PSTs’ understandings on how to teach and learn geometrical figures in mathematics classes after completion of their degree programs. This paper details the interpretation of the PSTs’ reflections on metric and topological spaces. From PSTs’ reflections, it was found that reflective questions helped individual PSTs to develop their understanding of matric and topological spaces, including giving the meaning of metric and topological spaces, and relating with real objects available in their daily environment. The findings have implications in teaching and learning metric and topological spaces. Keywords: Metric, topology, metric and topological spaces, pre-service mathematics teachers